A study on the effects of historical typhoon parameters on storm surge generation in San Pedro Bay using ADCIRC model - Villalba, Imee Bren O.
This study aims to determine the behavior of storm surge in San Pedro Bay generated by historical storms to understand the storm surge characteristics produced by different storm parameters. For this purpose, the Advanced Circulation Model (ADCIRC) is the hydrodynamic model used to simulate the storm surge in San Pedro Bay and the Holland 1980 Typhoon Model is used to model the pressure and wind distribution over the model domain. A total of 12 historical typhoons, including Typhoon Haiyan, are selected based on wind intensity and proximity to the study site as well as typhoons that have generated Storm Surges in the past. The observed data on typhoon wind and pressure of Typhoon Haiyan and measured high-water marks and timing of inundation of storm surge produced by the said typhoon along the coasts of San Pedro Bay are used in the validation of the modeling system. Validation of the typhoon model shows that Holland 1980 Typhoon Model overestimates the wind speed at the outer radius of the typhoon. Even with this limitation, the simulated water levels are in good agreement with the observed values in terms of the timing of peaks and high-water marks, especially at the inner portion of the bay. This shows that ADCIRC is capable of simulating the storm surge behavior at the inner part of the bay. Results show that storm surge is concentrated at Basey, Samar for typhoons with tracks north of the bay or directly crossing the bay due to the 4th quadrant winds of the typhoon while typhoons with tracks just South of the mouth of the bay have simulated storm Surges that have almost equal rate of decrease from the inner part to the mouth of the bay. The wind speed may be an indicator of the severity of the storm surge. Typhoon Haiyan 2013 with 110 kts (204 kph) maximum sustained) wind speed has simulated storm surge peak of 4-6 meters. Typhoon Agnes 1984 with 105 kts (195 kph) wind speed has simulated storm surge peak of 2-3 meters, and Typhoon Axel 1994 and Typhoon Cecil 1979 with 75 kts (139 kph) wind speed both have simulated peak surge of 1-2 meters, inside San Pedro Bay. Moreover, the results show that Tacloban in Leyte and Basey in Samar are the most storm Surge-prone areas, which may experience 1-6 meters of storm surge depending on the typhoon characteristics. Furthermore, a slow-moving typhoon has longer time to peak than fast-moving typhoons. Multiple regression analysis is also conducted to determine the predictor equation for Storm Surge considering typhoon parameters in Selected Stations along San Pedro Bay coasts. The results of this study are important in understanding the nature and severity of historical storm surge characteristics in San Pedro Bay, such as wind speed, typhoon track and forward speed, that can be used in disaster risk prevention and mitigation analysis, preliminary design of coastal protection structures, and in coastal Zone management of the bay. Moreover, the results of this study show that wind speed and direction as well as typhoon track relative to the coastline shape are important factors in the selection of synthetic typhoons for an archipelagic country Such as the Philippines that could be used in numerical analysis of Storm Surges specifically for the vertical Siting and engineering design of coastal protection Structures, and for coastal hazard assessment.